Respostas
respondido por:
3
Vamos lá :
2x² + x - 1 = 0
a = 2 ; b = 1 ; c = - 1
Δ = b² - 4ac
Δ = 1² - 4.2.(-1)
Δ = 1 - 8.(-1)
Δ = 1 + 8
Δ = 9 ⇔⇔ √Δ = 3
Utiliza a formula resolutiva (Bhaskara) :
x = - b ± √Δ / 2a
x = - 1 ± 3 / 2.2
x = - 1 ± 3 / 4
Raízes ...
x' = - 1 + 3 / 4 ⇔ x' = 2 ÷ 2 / 4 ÷ 2 ⇔ x' = 1 / 2
x'' = - 1 - 3 / 4 ⇔ x'' = - 4 / 4 ⇔ x'' = - 1
S = {- 1 , 1/2}
Espero ter ajudado !!!
2x² + x - 1 = 0
a = 2 ; b = 1 ; c = - 1
Δ = b² - 4ac
Δ = 1² - 4.2.(-1)
Δ = 1 - 8.(-1)
Δ = 1 + 8
Δ = 9 ⇔⇔ √Δ = 3
Utiliza a formula resolutiva (Bhaskara) :
x = - b ± √Δ / 2a
x = - 1 ± 3 / 2.2
x = - 1 ± 3 / 4
Raízes ...
x' = - 1 + 3 / 4 ⇔ x' = 2 ÷ 2 / 4 ÷ 2 ⇔ x' = 1 / 2
x'' = - 1 - 3 / 4 ⇔ x'' = - 4 / 4 ⇔ x'' = - 1
S = {- 1 , 1/2}
Espero ter ajudado !!!
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás